Dermatofibrosarcoma Protuberans-Like Tumor With COL1A1 Copy Number Gain in the Absence of t(17;22). (April 2017) - Saab, Jad; Rosenthal, Ian M.; Wang, Lu; Busam, Klaus J.; Nehal, Kishwer S.; Dickson, Mark A.; Hameed, Meera R.; Hollmann, Travis J.
Abstract : Abstract: A 57-year-old woman presented with a 3-year history of a progressive firm plaque on the right cheek. Skin biopsies revealed a bland, storiform, spindle-cell proliferation involving the deep dermis and subcutaneous fat. By immunohistochemistry, the tumor cells were diffusely positive for CD34 and caldesmon with multifocal reactivity for epithelial membrane antigen and focal, weak staining for smooth muscle actin. Retinoblastoma protein expression was not detectable in tumor cells by immunohistochemistry. An interphase fluorescence in situ hybridization analysis for platelet-derived growth factor B ( PDGFB ) gene rearrangement was negative. A single-nucleotide polymorphism array study detected 1) a gain of chromosome segment 17q21.33-q25.3 which overlapped the entire COL1A1 gene with a breakpoint at 17q21.33, approximately 250 Kb centromeric to the 3′ end of COL1A1 gene, 2) several segmental gains on chromosome 11, and 3) an RB1 gene locus with normal copy number and allele frequency. Although the current case resembles dermatofibrosarcoma protuberans, it is unique in that it demonstrates a copy number gain of chromosome 17q in the absence of fusion of COL1A1 and PDGFB genes and an unusual immunohistochemical staining profile. The morphologic and molecular findings suggest a novel molecular variant of dermatofibrosarcoma protuberans not detectable with standard fluorescence in situ hybridization for PDGFB rearrangement. This variant appears to respond to imatinib after 9 months of follow-up.